2017
DOI: 10.1155/2017/3868305
|View full text |Cite
|
Sign up to set email alerts
|

Tocotrienol‐Rich Fraction Ameliorates Antioxidant Defense Mechanisms and Improves Replicative Senescence‐Associated Oxidative Stress in Human Myoblasts

Abstract: During aging, oxidative stress affects the normal function of satellite cells, with consequent regeneration defects that lead to sarcopenia. This study aimed to evaluate tocotrienol-rich fraction (TRF) modulation in reestablishing the oxidative status of myoblasts during replicative senescence and to compare the effects of TRF with other antioxidants (α-tocopherol (ATF) and N-acetyl-cysteine (NAC)). Primary human myoblasts were cultured to young, presenescent, and senescent phases. The cells were treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…A study by Raspor et al, (Raspor et al 2005) demonstrate that treatment with Trolox, (α-tocopherol analogue) increased the cell viability, decreased intracellular ROS formation and suppressed DNA oxidation in Saccharomyces cerevisiae. In a human myoblast cell culture model, TRF treatment reduced the amount of intracellular ROS, reduced lipid peroxidation and decreased the number of cells undergoing late apoptotic events in senescent cells (Khor et al 2017).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A study by Raspor et al, (Raspor et al 2005) demonstrate that treatment with Trolox, (α-tocopherol analogue) increased the cell viability, decreased intracellular ROS formation and suppressed DNA oxidation in Saccharomyces cerevisiae. In a human myoblast cell culture model, TRF treatment reduced the amount of intracellular ROS, reduced lipid peroxidation and decreased the number of cells undergoing late apoptotic events in senescent cells (Khor et al 2017).…”
Section: Discussionmentioning
confidence: 94%
“…To prevent these damages, there are endogenous and exogenous antioxidants defence system that can eliminate the free radicals. Examples of endogenous antioxidants include the enzymes catalase and glutathione peroxidases which reduce hydrogen peroxide (Khor et al 2017), while the exogenous ones include vitamins C (Aumailley et al 2016) and vitamin E (Zadeh-ardabili et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Tocotrienol-rich fraction (TRF), a mixture of vitamin E analogs derived from palm oil, has garnered attention recently. Several reports have shown the potential of TRF in modulating A␤ metabolism [17], brain metabolites [18,19], antioxidant defense mechanisms [19,20], and cancer prevention [21]. Previously we have demonstrated that long-term supplementation (ten months) of TRF on APPswe/PS1dE9 double transgenic (Tg) mice (A␤PP/PS1), a mouse model of AD, reduced amyloid pathology in the brain [17].…”
Section: Introductionmentioning
confidence: 98%
“…The enzymatic components of the antioxidative defense system comprises several antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), enzymes of ascorbate-glutathione (AsA-GSH) cycle, ascorbate peroxidase (APX), monodehydroascorbate reductase (MDHAR), dehydroascorbate reductase (DHAR), and glutathione reductase (GR) [ 21 ] as well as non-enzymatic antioxidant systems such as bilirubin, glutathione (GSH), carotenoids, and vitamins C and E. The antioxidant enzymes operate in different subcellular compartments and respond in concert when cells are exposed to oxidative stress [ 22 ]. However, the effectiveness of the natural antioxidant network has been reported to decline with aging [ 23 , 24 , 25 ]. Thus, the purpose of this study is to compare the effects of TRF and α-TF supplementation, respectively, on the antioxidant levels of healthy individuals aged between 50 and 55 years.…”
Section: Introductionmentioning
confidence: 99%